Quality and Quality Standards In Construction: A Systematic Review - Nurhidayah, Azmy; Lum, Wai Wei (Penerbit UMP, 2021)
One of the customers’ satisfactory elements identified in construction is quality since the construction industry shifted from production-orientated management to customer orientated management. However, several issues are identified as a hindrance to achieving overall quality and can be caused due to low-quality construction materials and non-compliance to the standards. Therefore, before any further strategies to improve the quality of construction are determined, it is crucial to establish the fundamental knowledge on quality and its relevant aspects applicable in the construction industry. Hence, this paper seeks the definition of quality and quality standards by using the systematic review based on six-level of procedures. Based on the sources gathered, quality can be defined as the foreseeable degree of standardization and reliability with quality standard suitable to the client’s preference and thereby provide client’s approval, whereas quality standards is defined as to offer a reference in ensuring all construction activities comply to the adequate specifications set by authorized bodies. The definitions found provide practical implications for future work related to quality and project specification.